Rezultati preiskav fizikalnih lastnosti vzorcev iz lesa - Wallner, Edo (AR. Arhitektura, raziskave, 2006)
The article summarises the research, titled Conducting experiments on wooden samples at the Faculty of architecture during the coursework of the Construction and dimensioning, which dealt with tests conducted by second year students during experimental tutorials of the mentioned subject. The article presents an analysis of results obtained from testing wood she during the experimental tutorials. By applying the bending test students determined the elasticity module of unused spruce and oak wood and old spruce wood that had already been used in a structure. The obtained results were used as the basis for further analysis, by which we tested the authenticity of the measurements obtained experimentally by the student's. Deviations in measurements of the elasticity modules for various types of wood were very large, but simultaneously their values were practically equal. The results of the research prove that it is necessary to count on considerable deviations in physical properties of wood.
Keywords: konstruiranje; les; fizikalne lastnosti; preiskava materiala